The neutrophil-to-lymphocyte ratio and platelet-to-lymphocyte ratio in patients with neuromyelitis optica spectrum disorders and multiple sclerosis - Sun, Qingli; Ma, Xinran; Zhang, Linjing; Tian, Danyang (Frontiers in Neurology, 2025)
BackgroundThis study aimed to investigate the differences in neutrophil-to-lymphocyte ratio (NLR) and platelet-to-lymphocyte ratio (PLR) between patients with neuromyelitis optica spectrum disorders (NMOSDs) and multiple sclerosis (MS), as well as their potential associations with disease onset and progression.MethodsClinical, laboratory, and imaging data of NMOSD and MS patients admitted to Peking University Third Hospital were retrospectively analyzed. Blood test results within 1 week of new clinical symptoms or imaging abnormalities were used to calculate NLR and PLR. These ratios were compared with those of 100 healthy controls.ResultsA total of 79 NMOSD patients, 75 MS patients, and 100 healthy controls were included. The mean age of NMOSD patients was significantly higher than that of MS patients (p = 0.012). The Expanded Disability Status Scale (EDSS) scores at onset and after 1 year were significantly higher in NMOSD patients compared to MS patients (both p = 0.002). NLR was significantly elevated in NMOSD patients compared to both MS patients and healthy controls (p = 0.002 and p = 0.001, respectively), while no significant difference was observed between MS patients and healthy controls (p = 0.407). No significant differences in PLR were found among the three groups. After adjusting for age and gender, significant differences in NLR but not PLR remained between NMOSD and MS patients (p = 0.010 and p = 0.364). Receiver operating characteristic (ROC) analysis revealed an area under the curve (AUC) of 0.717 for NLR (p = 0.001, 95% CI: 0.636–0.798) and 0.567 for PLR (p = 0.152, 95% CI: 0.476–0.658) in distinguishing NMOSD from MS. In NMOSD patients, baseline and 12-month EDSS scores were significantly lower in the low NLR group (NLR < 2.44) compared to the high NLR group (NLR ≥ 2.44; both p = 0.008). Similarly, in MS patients, baseline and 12-month EDSS scores were significantly lower in the low NLR group (NLR < 1.68) compared to the high NLR group (NLR ≥ 1.68; both p = 0.003).ConclusionNLR may serve as a useful auxiliary tool for differentiating acute attacks or relapses of NMOSD from MS and is associated with prognosis in both NMOSD and MS patients.